Reconciling the discrepancy between the dehydration rates in mantle olivine and pyroxene during xenolith emplacement. (15th December 2019) - Xu, Yongjiang; Tang, Wenting; Hui, Hejiu; Rudnick, Roberta L.; Shang, Sheng; Zhang, Zhongtian
Abstract: Hydrogen concentration profiles through olivine and pyroxene in peridotite xenoliths carried in rift basalts from northern Tanzania (Lashaine, Eledoi, and Kisite localities) show bell-shaped distributions, indicating that diffusive hydrogen loss has occurred in all minerals. Homogeneous major element concentrations and equilibration of hydrogen between the cores of olivine and coexisting pyroxene suggest that hydrogen loss resulted from diffusive degassing during host magma emplacement. For these samples, hydrogen diffusivities in olivine and coexisting pyroxene must be within the same order of magnitude, similar to experimentally determined diffusivities, but in contrast to previous observations made on xenolithic peridotites. We demonstrate here, for the first time using natural samples, that significant differences in activation energy is likely the primary parameter that causes the discrepancy between hydrogen diffusion in olivine and pyroxene observed in different suites of mantle xenoliths. Because hydrogen diffuses faster in olivine than in pyroxene as temperature increases, hydrogen loss in the Tanzanian mantle xenoliths must have occurred at relatively low temperatures (∼750 to ∼900 °C), whereas hydrogen loss observed in previous xenolith studies likely occurred at higher temperatures (∼950 to >1200 °C). Thus, the diffusive loss of hydrogen in the Tanzanian mantle xenoliths may have occurred at shallow depths or at the Earth's surface.